2013
DOI: 10.1111/eos.12051
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of dental arch morphology in children with the syndrome of Crouzon or Apert

Abstract: The aim of this study was to compare changes in dental arch morphology between patients with Crouzon syndrome or Apert syndrome and controls. Children between 4 and 14 yr of age with Crouzon syndrome (n = 40) or Apert syndrome (n = 28) were compared with non-syndromic controls (n = 457) in terms of arch widths, depths, and length dimensions. Multilevel statistical modeling techniques were used to evaluate changes over time. Dental arch dimensions were found to be smaller in patients with Crouzon syndrome or Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 30 publications
1
23
0
3
Order By: Relevance
“…A previous study showed that subjects with maxillary constriction have increased airway resistance and resultant mouth breathing (Langford et al ). Furthermore, Reitsma et al reported that a low tongue posture, seen in patients with Apert syndrome, might contribute to the underdevelopment of the maxillary arch dimensions (Reitsma et al ). In this study, tongue thrusting was detected in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that subjects with maxillary constriction have increased airway resistance and resultant mouth breathing (Langford et al ). Furthermore, Reitsma et al reported that a low tongue posture, seen in patients with Apert syndrome, might contribute to the underdevelopment of the maxillary arch dimensions (Reitsma et al ). In this study, tongue thrusting was detected in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Apert syndrome is a congenital malformation characterized by craniosynostosis, cone‐shaped calvarium, mid‐facial hypoplasia, pharyngeal constriction, ocular manifestations and syndactyly or webbing of the hands and feet. The majority of the clinical features involve the head and neck; the main features found in the literature are listed in Table . There is also a wide range of other features affecting other systems within patients with Aperts noted in the literature, and these have been listed in Table .…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the clinical features involve the head and neck; the main features found in the literature are listed in Table . There is also a wide range of other features affecting other systems within patients with Aperts noted in the literature, and these have been listed in Table . After Crouzon syndrome, Apert syndrome is the second most common craniosynostosis syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Após a finalização do crescimento ósseo facial, realiza-se cirurgia ortognática (Le fort I, osteotomia mandibular), com objetivo de corrigir deformidades craniofaciais (26,27 Diversas manifestações bucais foram relatadas na literatura, como: hipodontia, dentes supranumerários, fissura no palato mole, apinhamento dentário severo na maxila, hipoplasia de maxila, mordida cruzada anterior e posterior severa, hiperplasia gengival, lábios hipotônicos e diversas anomalias dentárias (32,33).…”
Section: Síndrome De Apertunclassified
“…Dimensões reduzidas das arcadas requerem intervenção precoce e encaminhamento para uma equipe especializada (33).…”
Section: Síndrome De Apertunclassified